Effect of gestational age on growth of low birth weight infant: retrospective cohort study - Reva Audria Khairani; Tri Faranita; Yanti Harjono Hadiwiardjo; Fachri Razi Arslan (Medical Faculty of Brawijaya University, Indonesia, 2024)
Introduction: Growth is essential in children, especially in the first two years of life. History of low birth weight (LBW) and gestational age are known to be several factors that influence growth and relate to growth retardation. This study aims to analyze the effect of gestational age on the growth of LBW infants. Methods: An observational analytical study design with a retrospective cohort approach and quantitative study methods was conducted in September 2023. Subjects were gathered by simple random sampling. Twenty-four preterm infants and 24 full-term infants born from September 2021 to September 2022 who met the inclusion criteria were followed up. Subjects were weighed on a scale, and the results were plotted on the World Health Organization (WHO) weight-for-age growth chart. The plotted results are presented as a Z-score, which can be further categorized into two groups: severely underweight and underweight (growth not achieved), along with normal and risk of overweight (growth achieved). Result: Of the 48 subjects, the majority were male (66.67%), aged between 12-15 months (39,6%), born by cesarean section (83.3%), and had a history of exclusive breastfeeding (64.6%). Most subjects with a history of full-term and preterm LBW were in the normal category (70.8% and 75%, respectively). The result showed full-term LBW infants have 1.75 times greater risk of not achieving growth than preterm LBW with RR 1.750 (95%CI 0.588 to 5.207). Conclusion: Gestational age affects growth, with full-term infants at more risk of not achieving growth.